1998
DOI: 10.1021/bi980334p
|View full text |Cite
|
Sign up to set email alerts
|

15N NMR Relaxation Studies of Calcium-Loaded Parvalbumin Show Tight Dynamics Compared to Those of Other EF-Hand Proteins

Abstract: Dynamics of the rat alpha-parvalbumin calcium-loaded form have been determined by measurement of 15N nuclear relaxation using proton-detected heteronuclear NMR spectroscopy. The relaxation data were analyzed using spectral density functions and the Lipari-Szabo formalism. The major dynamic features for the rat alpha-parvalbumin calcium-loaded form are (1) the extreme rigidity of the helix-loop-helix EF-hand motifs and the linker segment connecting them, (2) the N and C termini of the protein being restricted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 64 publications
(139 reference statements)
4
28
2
Order By: Relevance
“…In both sites, the Ca 2þ ion in the center of the loop is coordinated by seven ligands sitting in the corners of a pentagonal bipyramid (Swain et al 1989). Results based on solution structures of a PV and b PV (Babini et al 2004) in the Ca 2þ -loaded and the apo (metal-free) form are summarized: (I) PV's Ca 2þ -loaded EF-hand domains and the linker region connecting the CD and EF domains are rather rigid structures; also the N-and C-termini of PV have a low intrinsic mobility (Baldellon et al 1998); (II) Differences in the structure of apo-and Ca 2þ -loaded forms of rat PV are small, mostly confined to the loop region. Thus, Ca 2þ binding does not require major structural rearrangements (Henzl and Tanner 2008); (III) The first two points also hold true for the Ca 2þ /Mg 2þ (EF) site in rat b PV, while the noncanonical CD site undergoes significant structural alterations, when Ca 2þ is removed from b PV (Henzl and Tanner 2007).…”
Section: Structural Aspects Of Parvalbuminsmentioning
confidence: 99%
“…In both sites, the Ca 2þ ion in the center of the loop is coordinated by seven ligands sitting in the corners of a pentagonal bipyramid (Swain et al 1989). Results based on solution structures of a PV and b PV (Babini et al 2004) in the Ca 2þ -loaded and the apo (metal-free) form are summarized: (I) PV's Ca 2þ -loaded EF-hand domains and the linker region connecting the CD and EF domains are rather rigid structures; also the N-and C-termini of PV have a low intrinsic mobility (Baldellon et al 1998); (II) Differences in the structure of apo-and Ca 2þ -loaded forms of rat PV are small, mostly confined to the loop region. Thus, Ca 2þ binding does not require major structural rearrangements (Henzl and Tanner 2008); (III) The first two points also hold true for the Ca 2þ /Mg 2þ (EF) site in rat b PV, while the noncanonical CD site undergoes significant structural alterations, when Ca 2þ is removed from b PV (Henzl and Tanner 2007).…”
Section: Structural Aspects Of Parvalbuminsmentioning
confidence: 99%
“…The best-studied example of a Ca 2+ sensor is the ubiquitously expressed CaM and still today, more CaM-dependent functions as well as CaM-modulated targets are being discovered (for recent reviews on CaM function, see [16,17]). On the other hand, the 15 NMR relaxation studies on the typical buffer PV revealed the solution structure to be relatively rigid [18], and both Ca 2+ - The three-dimensional structure of the EF-hand motif can be visualized by the right hand: the index finger represents the E-helix (residues 1 -10), the bent middle finger stands for the 12 amino acids of the canonical Ca 2+ -binding loop (10 - 21), and the thumb signifies the F-helix (19 -29). The seven oxygen ligands coordinating the Ca 2+ ion are located at the seven corners of a pentagonal bipyramid (modified from [25]).…”
Section: Ca 2+ Sensors Vs Ca 2+ Buffersmentioning
confidence: 99%
“…While the crystal structure of PV was known early on [2], in the last few years, more structures of PV in solution from different species or b PV structures have been published [37]. They include NMR studies on C and N relaxation of the Ca 2+ -loaded pike and rat PV [18], the apo (metalfree form) of rat a PV [38] and b PV [39]. The results from these studies can be briefly summarized as: (i) the Ca 2+ -loaded EF-hand domains of rat a PV as well as the linker region connecting the CD and EF domain are extremely rigid structures in comparison to those in CaM or CB-D28k and also the N and C termini of PV have a low intrinsic mobility [18].…”
Section: Relevant Parameters To Describe the Properties Of Ca 2+ Buffmentioning
confidence: 99%
See 1 more Smart Citation
“…The points at 752.4 ms and 1004.4 ms correspond to approximately 1.3 times the fastest and the slowest expected rate, respectively [18,25]. Estimates for the fastest and slowest rate were taken from a study on the related protein parvalbumin [27]. For R 2 we recorded 28 spectra with different relaxation times from which data sets corresponding to the conventional (18.4 (2x), 36.7, 73.4, 110.1 (2x), 146.8, 183.6 (2x), 220.3, 275.3 (2x), and 367.1 ms) and the optimized sampling scheme (18.4 (3x), 183.6 (5x), and 275.3 ms (5x)) were extracted.…”
Section: Methodsmentioning
confidence: 99%